LGG-22. EVALUATION OF IMMUNE AND GENOMIC CHARACTERISTICS IN PEDIATRIC OPTIC NERVE GLIOMA (ONG). (4th December 2020) - Campbell, Ashley A; Silverman, Andrew M; Moisander-Joyce, Hanna; Wu, Cheng-Chia; Mansukhani, Mahesh; Zanazzi, George; Turk, Andrew; Canoll, Peter D; Garvin, James H; Kazim, Michael; Gartrell-Corrado, Robyn D
Abstract: Pediatric optic nerve glioma (ONG) is a rare, sight-threatening tumor. We previously reported clinical, radiologic, histopathologic, and molecular characteristics of pediatric ONG patients treated at Columbia University Medical Center between 2000–2017. Here we evaluate this cohort and one additional patient using quantitative multiple immunofluorescence (qmIF) and next generation sequencing (NGS) using the Columbia Combined Cancer Panel (CCCP). For qmIF, 4 micron immuno-blank slides were stained for CD3, CD8, CD68, CD163, HLA-DR, and Olig2. QmIF images were analyzed and data were processed in R studio and compared based on tumor mutation and treatment history. QmIF failed in 1 case and CCCP failed in 2 cases. CCCP confirmed KIAA1549:BRAF fusions in 2 patients, identified NF1 in 2 patients, and demonstrated both a KIAA1549:BRAF fusion and SETD2 mutation in the added case. Qualitative analysis showed immune infiltrate across cases included macrophages (CD68+, 1.6–6.5% of all cells) and T cells (CD3+, 0.4% to 1.5%). Non-cytotoxic T cells (CD3+CD8-) comprised 60.7–100% of the T cell compartment. There was no difference when comparing mutation groups. However, patients who previously received radiation had increased CD3+, specifically CD3+CD8- cells compared to non-irradiated patients (p=0.01 and p<0.01, respectively) while CD3+CD8+ and CD68+ cells were not different between groups (p=0.49 and p=0.27, respectively). In summary, qmIF analysis showed increased tumor infiltration by non-cytotoxic T cells in previously irradiated pediatric ONG patients compared to non-irradiated patients, while there was no difference in macrophages of cytotoxic T cells. This type of analysis may be useful in designing immunotherapeutic strategies for pediatric ONG.